New-onset immune thrombocytopenic purpura (ITP) in pregnancy. (18th April 2012) - Wahba, J; Jaspal, R; Tailor, V; Garg, N; Joash, K
Abstract : Objective: Immune thrombocytopenic purpura (ITP) is a rare but important cause of thrombocytopenia in pregnancy, accounting for approximately 5% of cases of pregnancy-associated thrombocytopenia and affecting 1-2 in 1000 pregnancies.1 Its diagnosis is often complicated due to a wider differential diagnosis which includes gestational thrombocytopenia, TTP/HUS syndrome, pre-eclampsia and HELLP syndrome. We herein describe two cases of new-onset ITP in pregnancy. Case reports: Patient A, a Para 0+3 27 year African lady with known sickle-cell trait and no prior history of ITP, booked with platelets of 88, 000/μl and her platelet count was monitored throughout the pregnancy. She was induced at 38+1 due to intra-uterine growth restriction (IUGR) at which point her platelet count had fallen to 49, 000/μl. She delivered vaginally and did not require steroids or a platelet transfusion. Cord blood from the baby did not reveal a thrombocytopenia. Patient B, a Para 1 31 year old Sri-Lankan lady, booked with a platelet count of 257, 000/μl. She was admitted at 28 weeks of gestation with petechiae and bleeding gums and platelet count was found to be 2, 000/μl. A bone marrow trephine and biopsy were indicative of ITP and she received a platelet transfusion. She has been commenced on Prednisolone 60mg. She is currently 36 weeks gestation and is under regular surveillance. Discussion: Both cases illustrate the complexity of ITP. Early diagnosis is necessary in order to optimise anaesthetic options for delivery and reduce the risk of post-partum haemorrhage. Management of ITP in pregnancy is therefore challenging, requiring a multidisciplinary collaboration.